2017
DOI: 10.3389/fimmu.2017.01713
|View full text |Cite
|
Sign up to set email alerts
|

CD215+ Myeloid Cells Respond to Interleukin 15 Stimulation and Promote Tumor Progression

Abstract: Interleukin 15 (IL-15) regulates the development, survival, and functions of multiple innate and adaptive immune cells and plays a dual role in promoting both tumor cell growth and antitumor immunity. Here, we demonstrated that the in vivo injection of recombinant human IL-15 (200 µg/kg) or murine IL-15 (3 µg/kg) to tumor-bearing NOD-SCID-IL2Rg−/− (NSI) mice resulted in increased tumor progression and CD45+ CD11b+ Gr-1+ CD215+ cell expansion in the tumors and spleen. In B16F10-bearing C57BL/6 mice model, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…We have found that the depleting antibody loses its efficacy when IL-15cx is present ( Figure 4 ). This result is consistent with the promotion of CD11b + myeloid cells by IL-15 ( 54 , 55 ). However, in our study IL-15 or IL-15cx treatment has been shown to decrease MDSCs in tumor mice ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 89%
“…We have found that the depleting antibody loses its efficacy when IL-15cx is present ( Figure 4 ). This result is consistent with the promotion of CD11b + myeloid cells by IL-15 ( 54 , 55 ). However, in our study IL-15 or IL-15cx treatment has been shown to decrease MDSCs in tumor mice ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 89%
“…These data indicate that there is a novel mechanism capable of converting IL‐15 antitumor signals into tumor‐promoting signals. Similarly, a recent study reported that IL‐15 promoted the proliferation and insulin like growth factor‐1 (IGF‐1) production of IL‐15Rα + myeloid cells (CD45 + CD11b + GR‐1 + ) in lung cancer in immunodeficient mice [ 51 ]. Therefore, whether IL‐15Rα + TAMs exhibit similar functions in tumor types other than breast cancer requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 has been described in the pathology of various autoimmune diseases such as rheumatoid arthritis, autoimmune diabetes, inflammatory bowel disease and celiac disease [ 128 ]. In a melanoma mouse model, IL-15 promoted tumor progression by stimulating CD215+ myeloid cells [ 129 ]. In a B16 melanoma model, the upregulation of CCL4 and CCL5 recruited Tregs in a CCR5-dependent manner and promoted tumor progression [ 130 ].…”
Section: The Drawbacks Of Targeting Chemokines and Cytokinesmentioning
confidence: 99%